2011
DOI: 10.1002/ird.550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of small‐scale irrigation on household poverty: empirical evidence from the Ambo district in Ethiopia

Abstract: A study was conducted in the Ambo district of western Ethiopia in 2006 to understand the poverty reduction impacts of smallscale irrigation development, using the Indris irrigation system as a case study. The study was based on a survey of representative farm households with and without access to irrigation. The total sample size for the study was 222 (107 households with access to irrigation and 115 without). Data were analysed using descriptive statistics, the Foster, Greer and Thobeck poverty indices, and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
98
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 3 publications
18
98
2
Order By: Relevance
“…However, closely related literature which discusses adoption of small-scale irrigation in SSA is available. For instance, Bacha et al [17] conducted a study in the Ambo district of western Ethiopia to assess the impact of small-scale irrigation development on poverty reduction using a case study of Indris irrigation system. Their study found out that the incidence, depth and severity of poverty were significantly lower among households with access to small-scale irrigation.…”
Section: Related Literature On Small-scale Irrigation Farming and LIVmentioning
confidence: 99%
“…However, closely related literature which discusses adoption of small-scale irrigation in SSA is available. For instance, Bacha et al [17] conducted a study in the Ambo district of western Ethiopia to assess the impact of small-scale irrigation development on poverty reduction using a case study of Indris irrigation system. Their study found out that the incidence, depth and severity of poverty were significantly lower among households with access to small-scale irrigation.…”
Section: Related Literature On Small-scale Irrigation Farming and LIVmentioning
confidence: 99%
“…One such intervention is improving market information systems, by improving feeder roads or reducing the fees that traders pay to transport products between markets. Therefore, farmers' perception of their roads is one way to determine their access to market (Arias et al, 2013). In the present study, farmers' perceptions have been used as a proxy for market access, and 81% of the respondents perceived their roads to be in good condition.…”
Section: Discussionmentioning
confidence: 98%
“…According to Arias et al (2013), when market integration of producers is limited, interventions to reduce barriers to market participation will often have a greater payoff. One such intervention is improving market information systems, by improving feeder roads or reducing the fees that traders pay to transport products between markets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The irrigators had also better access to extension and credit services (Figure 9). In conclusion, irrigators are better in terms of food security status and other welfare indicators (Dereje Bacha et al, 2011). …”
Section: Benefits From Small-scale Rainwater Harvesting and Participamentioning
confidence: 99%